Biomedical Implications of Plant-based Principles as Antidepressants: Prospects for Novel Drug Development - Khushboo; Kumar, Abhishek; Sharma, Bechan (Mini Reviews in Medicinal Chemistry, 2022)
Background: Depression is the most common mental disorder. The symptoms of depression include loss of energy, changes in appetite, more or less sleep, anxiety, low concentration, uncertainty, restlessness, feelings of worthlessness, guilt, or despair, and thoughts of self-harm or suicide. In order to provide safe, efficient, and cost-effective medication, the plant-based principles in isolation or combination with traditional antidepressants are gaining increasing attention for depression therapy. Methods: This study includes the information regarding the present review and its contents collected from published literature materials in different international journals. We have used different search engines such as PubMed, Medline, ResearchGate, Google Semantic Scholar, and Science Direct. For this purpose, the data obtained were properly organized and analyzed to include in this article. Results: Most of the phytomolecules isolated from the medicinal plants display antidepressant effects through the synaptic regulation of levels of neurotransmitters such as dopamine, serotonin, and noradrenaline in different parts of the brain. The mechanism of action of phytomolecules also involves negative regulation of the activities of monoamine oxidase (MAO) and acetylcholinesterase (AChE) and prevention of hyperactivity of the hypothalamic-pituitary-adrenal (HPA) axis. In addition, the strong antioxidative and anti-inflammatory potential of these phytochemicals offer synergy to their antidepressant as well as antipsychosomatic functions. Conclusion: The application of phytochemicals has proved it to be a safe, cost-effective, and efficient therapeutic agent to treat patients suffering from mild to severe states of depression and other psychiatric disorders. The potential phytochemicals may be further optimized using in silico tools to develop better antidepressants and antipsychotic agents in the future.
Keywords: antioxidants